2018
DOI: 10.18060/21634
|View full text |Cite
|
Sign up to set email alerts
|

Peer Support Groups: Evaluating a Culturally Grounded, Strengths-Based Approach for Work With Refugees

Abstract: Many refugees will face unique socio-emotional stressors before, during, and after resettling in their new home country. The program presented herein focuses on the use of para-professionals, peer educators, from within refugee communities to build upon the Center for Torture and Trauma Survivors Clubhouse model. Group leaders seek to provide supports that will: 1) decrease feelings of isolation; 2) build community networks and; 3) increase feelings of empowerment within the community. To accurately represent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…In contrast, other experiences, such encounters with continued discrimination could engender feelings of uncontrollability, and in addition challenge perceptions of the supports available to build a new life (Jorden et al, 2009 ). Perhaps for this reason, the creation of community social networks that decrease refugees' feelings of isolation and increase feelings of empowerment play an important role in their capacity to adapt to a new setting and to demonstrate resilience in the face of subsequent stressors (Block et al, 2018 ).…”
Section: Scenario 2 the Refugee Experiencementioning
confidence: 99%
“…In contrast, other experiences, such encounters with continued discrimination could engender feelings of uncontrollability, and in addition challenge perceptions of the supports available to build a new life (Jorden et al, 2009 ). Perhaps for this reason, the creation of community social networks that decrease refugees' feelings of isolation and increase feelings of empowerment play an important role in their capacity to adapt to a new setting and to demonstrate resilience in the face of subsequent stressors (Block et al, 2018 ).…”
Section: Scenario 2 the Refugee Experiencementioning
confidence: 99%
“…It is common for researchers and physicians to focus on the trauma that refugees have passed through; either before resettlement including political violence and war, during their routes to the host country and after their resettlement including their struggles with a new language, new social life, discrimination and integration. Therefore, any refugee will have been subject to some form of trauma in their lives either directly or indirectly (Block et al, 2018), and this explains why the majority of interventions focus on treatment of symptoms such as Post Traumatic Stress Disorder (PTSD) (ibid). Many interventions, yet, still lack the culturally sensitive, low threshold element that is proven to help refugees a great deal (Zellmann, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies show that it is of utmost significance not to label all refugees as suffering from some type of pathology because they are all individuals going through extraordinary circumstances (Block et al, 2018). Health care professionals should be conscious of cultural differences that may arise when interacting with refugees and to seek strengths-based and empowerment-based approaches for work with them (Abi Jumaa et al, 2019;Block et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While the content design and delivery were developed within a culturally sensitive 66 co-produced format, the composition of peer interventions that were group based, were 67 also co-produced. The studies reported on the importance of having a homogeneous com-68 position in terms of group membership, and this extended beyond ethnicity, with gender 69 and even age often sought out (Block et al, 2018;Stewart et al, 2012;Tol et al, 2020). The 70 Steward et al (2012, p. 525) findings exemplify this; 71 "Participants appreciated that female and male refugees met separately and that the 72 Somali and Sudanese refugees had separate groups.…”
mentioning
confidence: 99%
“…In terms of the intervention's peers were trained in, two models were based on train-84 ing peers in peer support and then providing them with mobile phones with credit to 85 practice offering support to each other in order build social capital (Koh et al, 2018;Wol- (Block et al, 2018); Culture-Sensitive and Resource Oriented Peer (CROP); (Renner 90 et al, 2011), ALMA (Amigas Latinas Motivando el Alma/Latina Friends Motivating the 91 Soul); (Tran et al, 2013), Self Help Plus ( Purgato et al, 2021;Tol et al, 2020) and Pro-92 gramme Management Plus (Gaaff et al, 2020). The delivery and content of interventions 93 was diverse, for example, Paloma et al (2020a) reported including issues such as migratory 94 mourning (e.g., social network, language, culture, and status), and identifying personal 95 strengths and community resources to cope with these issues.…”
mentioning
confidence: 99%